Drilling pipe release additive based on petroleum coke distillate - Vega Mejía, Rubén Darío (2020)
The fundamental objective of this research was to develop a pipe-releasing additive based on petroleum coke distillates. For this, a soxhlet extractor was used using xylene as an organic solvent. Subsequently, the formulation of the different pipe release pills (with commercial additive and coke distillate) was established, studying the effect of these on the properties of the different plasters generated from a 100% mineral oil drilling fluid through tests quality at laboratory level, such as: lubricity coefficient, weight loss and reduction of the thickness of the plaster. An Anova was applied for an experimental design of simple randomized blocks, consisting of four blocks (pills), three treatments (quality tests) and four repetitions; and a Duncan Test (α = 0.05), showing that the treatments with coke distillate presented better performance compared to the commercial pill. It was concluded that the differences between the pills is due to the mechanism of action of each one.